Protective functions of salvianolic acid B in PC-12 cells against hydrogen peroxide-triggered damage by mediation of microRNA-26a - Niansheng Liu; Mingfu Fan (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Spinal cord injury (SCI) can lead to varying degrees of sensory and motor dysfunction. Salvianolic acid B (Sal-B) is the dominating bioactive constituent of Danshen, which has been reported to alleviate liver fibrosis and exert neuroprotective effects. But, the influence of Sal-B in SCI remains mysterious. The research planned to delve the protective function of Sal-B in hydrogen peroxide (H2O2)-caused PC-12 cell injury. H2O2-caused PC-12 cells injury model was built, CCK-8, Transwell and flow cytometry experiments were enforced to assess cell proliferation, migration and apoptosis. The microRNA (miR)-26a plasmid and the matching control were transfected into PC-12 cells, subsequently, the influence of miR-26a inhibition in H2O2-corrupted PC-12 cells was evaluated. The cell growth-correlated factors and PI3K/AKT and MEK/ERK pathways were assayed through western blot assay. Results corroborated that Sal-B eased H2O2-evoked injury in PC-12 cells. Ascended miR-26a was monitored in Sal-B and H2O2-exposed cells. MiR-26a inhibition annulled the protective action of Sal-B in H2O2-corrupted cells. The protective function of Sal-B was enabled through activating PI3K/AKT and MEK/ERK pathways. These findings delineated that Sal-B protected PC-12 cells against H2O2-caused injury through ascending miR-26a via initiating PI3K/AKT and MEK/ERK pathways.HighlightsH2O2 causes PC-12 cell injury;Sal-B eases H2O2-caused PC-12 cell injury;Sal-B protects PC-12 cells against H2O2-caused injury via elevating miR-26a;Sal-B activates AKT and MEK/ERK pathways via modulating miR-26a.